A journey following childbirth trauma. (30th December 2022) - Pitchford, Claire
Back in 2015 I gave birth to my first child and had a complicated birth and postnatal experience. I suffered birth trauma and I was diagnosed with post-traumatic stress disorder (PTSD) when my baby was eight months old. Whilst I mostly dealt with the mental and physical difficulties of PTSD with therapy, what I was not prepared for nor do I think I'll fully get over, was the effect the investigation report into my birth had on my mental well-being. Writing became part of my therapy. In fact, my therapist prescribed it as 'homework' at the time. I had not written creatively prior to this and I didn't understand how writing would benefit my well-being positively. What I learned along the course of my therapy was the power the written word has in healing a hurt and damaged soul. I maintained a blog and could see my healing progress as time moved on. Therapy for me has since finished but I still try to write when I can. I do this often around my child's birthday as I struggle most with memories from the time of birth. I write when I feel emotionally overwhelmed and I feel a release in this process. Whilst I do not think my pieces are award winning, each holds a period of time when my emotions ran high and to me, they have become precious notes capturing the rawness unique to my experiences and where others may also find some comfort in that they're not alone. I will share some of these pieces with you. Dedicated to anyone who has suffered birth trauma or from the effects of poor communication and lack of acknowledgement around psychological harm, this is for you.